2006
DOI: 10.1128/aem.72.2.1355-1363.2006
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Lysogeny and Pseudolysogeny in Vibrio harveyi Siphovirus-Like Phage 1

Abstract: Exposure of Vibrio harveyi (strain VH1114) to V. harveyi siphovirus-like phage 1 (VHS1) resulted in the production of a low percentage of lysogenized clones of variable stability. These were retrieved most easily as small colonies within dot plaques. Analysis revealed that VHS1 prophage was most likely carried by VH1114 as an episome rather than integrated into the host chromosome. In the late exponential growth phase, lysogenized VH1114 continuously produced VHS1 but also gave rise to a large number of cured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
4
32
0
1
Order By: Relevance
“…We took the precaution of isolating our phage-resistant mutant by screening rather than selection so that the mutant bank would not be subject to artifactual effects, such as lysogeny or pseudolysogeny (20). The phage employed in the isolation of our resistant strain has not been documented to be lysogenic (19).…”
Section: Discussionmentioning
confidence: 99%
“…We took the precaution of isolating our phage-resistant mutant by screening rather than selection so that the mutant bank would not be subject to artifactual effects, such as lysogeny or pseudolysogeny (20). The phage employed in the isolation of our resistant strain has not been documented to be lysogenic (19).…”
Section: Discussionmentioning
confidence: 99%
“…In shrimp ponds, Vibrio harveyi (VH) is a common bacterial species that sometimes causes luminescent disease, although luminescence is not a requirement for shrimp pathogenicity. On the other hand, it has been shown that bacteriophages can sometimes lysogenize VH and alter their pathogenicity for shrimp [1][2][3] . Increased virulence due to lysogeny is well known for human pathogens 4 , including Salmonella enteritica 5 , Vibrio cholerae, 6 and Staphylococcus aureus 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the phage is carried in the lysogens as an episome, cured isolates can be obtained at high rates by isolation of single colonies upon subculture (14). Random clones representing approximately 25% of the VHS1 genome were previously sequenced and deposited in GenBank (26).Vibrio harveyi 1114GL (VH0) that has been lysogenized by VHS1 (VH1) is Ͼ100 times more lethal to the black tiger shrimp than VH0 (13,14). In addition, culture supernatant solutions from VH1 are highly toxic for the black tiger shrimp (Penaeus monodon) but not for the whiteleg shrimp (Penaeus [Litopenaeus] vannamei) (13).…”
mentioning
confidence: 99%
“…Vibrio harveyi 1114GL (VH0) that has been lysogenized by VHS1 (VH1) is Ͼ100 times more lethal to the black tiger shrimp than VH0 (13,14). In addition, culture supernatant solutions from VH1 are highly toxic for the black tiger shrimp (Penaeus monodon) but not for the whiteleg shrimp (Penaeus [Litopenaeus] vannamei) (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation